Resiko Perbankan Syariah Pada Suatu Analisis Pembiayaan di Bank Syariah - Andrian Saputra (Publikasi Inspirasi Indonesia, 2024)
This article discusses the risks of sharia banking in an analysis of financing in sharia banking. Sharia banks will continue to manage various opportunities with various risks and for the realization of sharia banking activities. Therefore, implementing risk management in sharia banking is very important to identify, measure and control the various risks that will be faced. The research method in this paper uses the Library Research method, where this method uses a type of secondary data collection obtained from existing data sources. The purpose of this article is to discuss and examine in more depth the risks related to sharia banking boards, both hypothetically and in practice. In a context like this, of course, the perspective and opportunities in sharia banking, the description of the quality of transactions in sharia banks, the grouping of types of management in sharia banks, as well as the implementation of transaction activities, both administration and risk, in sharia banking. In sharia banking, the sharia banking activity cycle must utilize prudential principles to make it easier to recognize, search for, monitor and measure risks. In the cycle stages of sharia banking, it is carried out by recognizing risks, assessing and estimating opportunities, and monitoring risks. Risk factors are very important for Islamic banks to ensure that financial markets develop rapidly.